Permaculture as Richard Bauckham’s Living with Other Creatures: : A Prefigurative Symbol for Messianic Redemption in Nature - Bierma, Troy (De Ethica, 2025)
To have moral standing to blame is to have a right to blame. But what kind of right is it, and what follows from having or lacking standing? I will argue that moral standing to blame should be understood as a power according to Wesley Hohfeld’s classification of rights (1913). It is a normative power to call for an uptake of blame from someone who is liable to blame, i.e., someone who is blameworthy. The function of standing norms, I will argue, is to protect the freedom and interests of persons who are or could be blamed. I make three further claims in distinction to recent scholarship on standing: I argue that the concept of standing does not apply at all to private blame, only to expressed blame; I claim that standing cannot be understood as only a privilege-right; and I argue that there is not a conceptual asymmetry between standing to blame and standing to forgive.